Mary Louise Solves a Mystery - Baum, L. Frank (Saga Egmont, 2021)
Originally published under the pseudonym Edith van Dyne, ‘Mary Louise Solves a Mystery’ is the third book in the popular children’s series by prolific author L. Frank Baum. Mary Louise is travelling around Italy with her grandpa Jim when she comes across unhappy young heiress Alora Jones. Alora’s mother died not long ago, leaving Alora and her inheritance under the control of her moody and secretive ex-husband in Italy. Sensing a mystery, Mary Louise and her friend and trainee detective Josie O’Gorman are soon on the case.